Securing biometrics applications - Shoniregun, Charles A. (Springer Science+Business Media, LLC, 2008)
Biometrics is becoming increasingly common in establishments that require high security such as state security and financial sectors. The increased threat to national security by terrorists has led to the explosive popularity of biometrics. A number of biometric devices are now available to capture biometric measurements such as fingerprints, palm, retinal scans, keystroke, voice recognition and facial scanning. However, the accuracy of these measurements varies, which has a direct relevance on the levels of security they offer. With the need to combat the problems related to identity theft and other security issues, society will have to compromise between security and personal freedoms. Securing Biometrics Applications investigates and identifies key impacts of biometric security applications, while discovering opportunities and challenges presented by the biometric technologies available. This volume also includes new biometric measures for national ID card, passport and centralized database system. Securing Biometrics Applications is designed for a professional audience, researchers, and practitioners. This book is suitable for advanced-level students as a secondary text or reference book in computer science.